2017
DOI: 10.12968/bjcn.2017.22.6.289
|View full text |Cite
|
Sign up to set email alerts
|

Introducing community integrated nursing teams: How one Clinical Commissioning Group applied an evidence-based approach

Abstract: Introducing community integrated nursing teams: How one ClinicalCommissioning Group applied an evidence-based approach http://researchonline.ljmu.ac.uk/6534/ Article LJMU has developed LJMU Research Online for users to access the research output of the University more effectively. Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Users may download and/or print one copy of any article(s) in LJMU Research Online to facilitate their pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…A positive feeling for building cohesion in terms of improved systems reducing duplication of roles was found. This is consistent with prior studies that reveal the concepts of development of working relationships, learning, networking and understanding differing roles subsequently improved responses to patients’ needs across the health and care economy (Lees et al , 2017; Fraser, 2019).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…A positive feeling for building cohesion in terms of improved systems reducing duplication of roles was found. This is consistent with prior studies that reveal the concepts of development of working relationships, learning, networking and understanding differing roles subsequently improved responses to patients’ needs across the health and care economy (Lees et al , 2017; Fraser, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, Britnell (2019) points out universally the truism of “there is no healthcare without the workforce” (p. 9) is acknowledged yet inadequately addressed. The voice of the workforce is imperative as Lees et al (2017) indicate IC success is not solely the reduction of hospital admissions but should also include patient experience, professional opinion and experiences of staff and clinicians.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a systematic review of the literature, Mackie and Darvill (2016) identified that co-location of staff during the development of integrated teams was widely viewed as essential for different professions to develop collaborative working relationships. Further studies have linked co-location to improved communication and a greater understanding of job roles (Lees et al , 2017). However, co-location alone does not necessarily result in measurable improvements in collaborative working across professional boundaries (Taylor, 2012; SCIE, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although the evidence of the impact of integration strategies on patient outcomes is difficult to find, most would argue that this does not mean that health and care staff are not willing to work together to deliver the best possible care for service users. The issue of inter-professional barriers, such as a lack of trust and understanding of each other’s roles, is increasingly recognised as an area of concern which needs to be addressed in order to achieve the aims of integration (Nasir et al , 2013; Mangan et al , 2015; Lees et al , 2017). The government has argued for moving beyond stumbling blocks to making integration happen whilst exploring the barriers that undoubtedly exist (Department of Health, 2012a).…”
Section: Introductionmentioning
confidence: 99%